Fulminant Myocardial Involvement in Neonatal Echovirus-induced Sepsis. Two Autopsy Cases. Issue 2 (20th July 2021) - Callon, Domitille; Guedra, Aurélien; Lebreil, Anne-Laure; Rambaud, Caroline; Fornés, Paul; Andreoletti, Laurent
Abstract : Group-B Enteroviruses, such as Echoviruses, are a common cause of infections in neonates but fatal myocarditis during Echovirus-induced sepsis have been rarely reported. We report on 2 cases of neonatal Echovirus-related sepsis with myocarditis. Fatal cardiorespiratory failure occurred in both cases. Autopsies and thorough histologic and microbiologic investigations evidenced Echoviruses 5- and 11-induced myocarditis as the cause of death.